The Existence of the Ji'alah Contract - Syarifah, Ma’isyatus; Arodha, Dianidza (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2022)
The times are growing, as it is today. Many modifications and innovations have made the practice of renting transportation even more developed. So new discussions are needed to apply the law to existing phenomena. In general, the lease agreement is known to be classified as an ijarah contract, but in a different case, the lease contract is included in a ji’alah contract, not an ijarah. This study aims to analyze the existence of jialah contracts in everyday life. By using an approach and literature review method, this study selected informants according to the non-purposive sampling method. The data validity technique used triangulation of sources and techniques. The results of this study found the practice of jialah contracts in the world of transportation, including vehicle fees, transportation rentals, and competitions.